Gastropod Community Structure in the Coastal Waters of Lalang Village Siak Regency - William Simamora; Zulkifli Zulkifli; Syafruddin Nasution (Tropical Marine Enviromental Sciences, 2024)
Class Gastropods is the largest class of the Phylum Mollusca. Changes influence the gastropod community structure in terms of environmental factors. This study was conducted in the coastal waters of Lalang Village, Sungai Apit District, Siak Regency, in June 2022, aiming to determine the structure of the Gastropod community, which includes species, density, diversity, uniformity, dominance, and distribution pattern, and water quality. Sampling using the line transect method was carried out at four stations. The study found eight species of gastropods; the gastropod density values obtained at each research station were 3.57-4.84 ind/m2. The value of the gastropod diversity index (H') was categorized as medium, the gastropod uniformity index (E) was classified as high, and the dominance index value (C) indicated that there were no dominant species in the waters. The distribution pattern of gastropods between observation stations is clustered